The medium as an enabler for the creation of a reading environment - Paredes Infante, Belsy Norela; Torres Navarro, Sandra Milena (Rastros Rostros, 2002)
The formation of readers begins from the very moment of conception and is a process that continues throughout life. Early and second childhood are the beginning of such a wonderful gift of life and it depends on a welcoming environment and the motivation of parents and nannies the taste that the child gets for reading in his schooling.